An analysis of maṣlaḥah based resolutions issued by Bank Negara Malaysia - Eldersevi, Suheyib; Haron, Razali (Emerald Group Publishing Ltd., 2019)
Purpose: This study aims to examine the resolutions issued by the Sharīʿah Advisory Council of Bank Negara Malaysia (SAC-BNM), which have recognized maṣlaḥah (public interest) as the basis of ruling to see the extent of its usefulness to the public and the extent of its adherence to the maṣlaḥah parameters. The study will also look into the opposing opinion to identify the basis of rejection and overall implication on Islamic finance based on opposing opinions of SAC-BNM and other bodies of collective ijtihād (juristic interpretation). Design/methodology/approach: The study uses a qualitative approach by analyzing the SAC-BNM resolutions, which have been resolved based on maṣlaḥah. The study also applies the comparative approach by comparing the fatwa (Sharīʿah pronouncement) issuing bodies of Malaysia and the Gulf Cooperation Council countries. Furthermore, the secondary data is obtained from sources such as uṣūl al-fiqh (theory of Islamic jurisprudence) books, papers and relevant internet sources. Findings: The study found that SAC-BNM’s resolutions are in line with some of the major maṣlaḥah parameters mentioned in the uṣūl al-fiqh sources i.e. must not contradict with the Qurʾān and the Sunnah. While looking at the other two criteria of being in line with ijmāʿ (consensus) and having a general impact, such resolutions might not fulfill the criteria of valid maṣlaḥah considering, respectively, the stand of collective ijtihād or the impact on the group of customers and institutions. Originality/value: Most available shari’ah (Islamic law) research considers the perspective of fiqh (Islamic jurisprudence) while analyzing the issue of maṣlaḥah. This study aims to conduct analysis based on uṣūl al-fiqh. Moreover, maṣlaḥah itself is a broad concept, which can be abused. Hence, this study discusses the parameters of maṣlaḥah to understand the validity of an important juristic tool in Sharīʿah. © 2020, Suheyib Eldersevi and Razali Haron.